Alcohol and football - Maughan, R. J. (Journal of Sports Sciences, 2006)
The use of alcohol is often intimately associated with sport, and the association is particularly strong in football. As well as providing a source of energy, alcohol (ethanol) has metabolic, cardiovascular, thermoregulatory, and neuromuscular actions that may affect exercise performance. Its actions on the central nervous system, however, result in decrements in skill and behavioural changes that may have adverse effects on performance. There is also evidence of dose-dependent decrements in aerobic capacity. Although the mechanisms are not well understood, the aftermath of alcohol use (hangover) may also adversely affect performance for many hours after intoxication. Alcohol intoxication may adversely affect the player's dietary choices by displacing carbohydrate from the diet at a time when restoration of glycogen stores should be a priority.